Design and Manufacturing of soft robotics mechanisms: improving the reliability of pneumatic-based solutions - Alves, Samuel José dos Reis (2020)
Dissertação de Mestrado Integrado em Engenharia Mecânica apresentada à Faculdade de Ciências e Tecnologia